Gingival recontouring by provisional implant restoration for optimal emergence profile: report of two cases - Son, Mee-Kyoung (Korean Academy of Periodontology, 2011)
PURPOSE: The emergence profile concept of an implant restoration is one of the most important factors for the esthetics and health of peri-implant soft tissue. This paper reports on two cases of gingival recontouring by the fabrication of a provisional implant restoration to produce an optimal emergence profile of a definitive implant restoration. METHODS: After the second surgery, a preliminary impression was taken to make a soft tissue working cast. A provisional crown was fabricated on the model. The soft tissue around the implant fixture on the model was trimmed with a laboratory scalpel to produce the scalloped gingival form. Light curing composite resin was added to fill the space between the provisional crown base and trimmed gingiva. After 4 to 6 weeks, the final impression was taken to make a definitive implant restoration, where the soft tissue and tooth form were in harmony with the adjacent tooth. RESULTS: At the first insertion of the provisional restoration, gum bleaching revealed gingival pressure. Four to six weeks after placing the provisional restoration, the gum reformed with harmony between the peri-implant gingiva and adjacent dentition. CONCLUSIONS: Gingival recontouring with a provisional implant restoration is a non-surgical and non-procedure-sensitive method. The implant restoration with the optimal emergence profile is expected to provide superior esthetic and functional results.